Psychotic-like experiences among university female students in Qatar: A qualitative-phenomenological study - Yehya, Arij; Khaled, Salma M.; Sommer, Iris E. C.; Woodruff, Peter; Daher-Nashif, Suhad (Frontiers in Psychiatry, 2022)
Background and aims Psychotic-like experiences (PLEs) represent hallucinatory or delusional experiences that fall below the threshold of a diagnosable psychotic disorder. Although PLEs are common across spectrum of psychiatric disorders, they also have been commonly reported in the general population. In this study, we aim to describe types of PLEs among university students in Qatar. Furthermore, we aim to examine how students frame, explain and deal with these experiences, as well as understand how culture and religion may shape the way students attribute and respond to these experiences. Method This study used a qualitative phenomenological approach. For collecting the data we conducted semi-structured interviews based on the Questionnaire for Psychotic Experiences (QPE). The QPE is a valid and reliable tool to assess phenomenology of psychotic-like experiences. The questionnaire was translated to Arabic, tested, and validated in Qatar (a fast developing Muslim country in the Arabian Peninsula). We conducted the interviews in Arabic with 12 undergraduate female students, of different Arab nationalities, at Qatar University, which is the only national university in Qatar. Interviews were transcribed verbatim and two authors conducted content-thematic analysis separately, as a strategy to validate the findings. The study was part of a larger nationally funded project that was approved by Qatar University Institutional Review Board before any interviews were conducted with any of the participants. Results The psychotic-like experiences were prevalent in our non-clinical sample. The content-thematic analysis revealed the following main themes about these experiences: type, impact on daily function, frequency, immediate reaction, attributional style, assumptions about the root cause of these experiences, other associations and religious links to experiences. Religion and culture played a role in shaping the types of hallucinations and some of the delusions. Conclusions Our findings support the importance of culture and religion in relation to the types and explanations that students provided when describing psychotic-like experiences. Notably, it was a common among those who reported having these experiences to normalize and link PLEs to real life events. This maybe a defense mechanism to protect the self against stigma of mental illness and from being labeled as ‘abnormal’.